Regional management — Potentials, limits and perspectives: Results of a study in Saxony-Anhalt in the framework of a diploma thesis (2003) in the course “Geography” at the Free University of Berlin - Schäffer, Verena (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
The concept of regional management has gained more and more importance over the last decade. Based on empirical studies of three regions in Saxony-Anhalt, the concept of regional management was closely examined from a theoretical and practical perspective to determine the efficiency of this concept. The results of this analysis are presented in this essay. The structures of the regional management of the three case studies are presented and quality criteria are identified. Problems of implementation are also indicated. On this basis, recommendations are drawn for the future implementation of regional management concepts.